Chronic thromboembolic pulmonary hypertension: initial experience of patients undergoing pulmonary thromboendarterectomy - Plácido, Rui (2022)
© 2021 Published by Elsevier España, S.L.U. on behalf of Sociedade Portuguesa de Cardiologia. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).